ROLE OF VYOSHADI GUGGULU IN MEDOROG (OBESITY) ASSOCIATED WITH DYSLIPIDEMIA: A CASE STUDY - Sharma, Nitin; Deshpande, Sadanand V. (International Journal of Ayurveda and Pharma Research, 2015)
Medorog (obesity) has been described extensively in various Ayurvedic texts. Acharya Charak has described Medorog among the eight most unwanted diseases (Ninditpurush) Samtarpanajanita Roga. Medorog can be compared with obesity in modern terminology. Obesity is the condition in which excess body fat has accumulated to the extent that it may have an adverse effect on health, leading to reduced life expectancy and increased health problems. The most important cause of obesity is an energy imbalance between the calories consumed and calories expended which leads to the accumulation of fat. In 21st century, obesity is not less than any epidemic targeting more and more people every day. Over one out of every five persons in the world is obese. Obesity is such a disease which provides the platform for many life threatening hazards like dyslipidaemia etc. A case of Medorog associated with dyslipidaemia managed successfully by Ayurvedic treatment is reported here. A 49 year old female having sign and symptoms of Medorog was treated with Vyoshadiguggulu, a formulation of Ashtang Hridya in the dosage of 1gm. three times a day with 1 table Spoon of honey and lukewarm water for 90 days. Patient showed remarkable improvement in Obesity and dyslipidaemia after the treatment.